2017
DOI: 10.9734/jalsi/2017/32503
|View full text |Cite
|
Sign up to set email alerts
|

Botanical Pesticides in Management of Common Bean Pests: Importance and Possibilities for Adoption by Small-scale Farmers in Africa

Abstract: Botanical Pesticides (BPs) have been cited and are used as alternative to synthetic pesticides in agricultural systems worldwide. The BPs are believed to be safe to the environment and are used in pest control to avoid pesticidal pollution, which is a universal problem. In this review, authors provide comprehensive information on the use of BPs in management of common bean pests in Africa. This piece of literature is useful due to major negative side effects to the environment as well as human health arising f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Botanical pesticides typically exhibit broad spectrum antimicrobial activity, in most cases being nonselective, so they can potentially affect the soil microbiota population (Bhat et al, 2012;Conti et al, 2014;George et al, 2010;Spyrou et al, 2009). Nonetheless, as discussed earlier, these compounds offer considerable advantages, compared to the synthetic compounds currently used, and are promising for use in sustainable agriculture (Chowdhury et al, 2015;Dar et al, 2014;Dubey et al, 2010;Karani et al, 2017;Khaliq et al, 2014;Xu et al, 2015). Their rapid breakdown in the environment, together with low accumulation in the soil organic matter, can help to decrease the degradation of agricultural soils (Ansari et al, 2012;Archana Singh, 2014;Blázquez, 2014;Carrubba and Catalano, 2009;Pavela and Benelli, 2016;Raja, 2013).…”
Section: Future Trends In Sustainable Agriculturementioning
confidence: 99%
“…Botanical pesticides typically exhibit broad spectrum antimicrobial activity, in most cases being nonselective, so they can potentially affect the soil microbiota population (Bhat et al, 2012;Conti et al, 2014;George et al, 2010;Spyrou et al, 2009). Nonetheless, as discussed earlier, these compounds offer considerable advantages, compared to the synthetic compounds currently used, and are promising for use in sustainable agriculture (Chowdhury et al, 2015;Dar et al, 2014;Dubey et al, 2010;Karani et al, 2017;Khaliq et al, 2014;Xu et al, 2015). Their rapid breakdown in the environment, together with low accumulation in the soil organic matter, can help to decrease the degradation of agricultural soils (Ansari et al, 2012;Archana Singh, 2014;Blázquez, 2014;Carrubba and Catalano, 2009;Pavela and Benelli, 2016;Raja, 2013).…”
Section: Future Trends In Sustainable Agriculturementioning
confidence: 99%
“…They are convenient to use, since they are biodegradable, environmentally-friendly and safe. Hence, they are potentially suitable for use as pure compounds or in an integrated form, as some are specific while others can have multiple target sites (KARANI et al 2017, CAMPOS et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, behind these activity of botanical-based pesticide against of aphid and mite, it may be act as induce acquired plant resistance, similarly, Karani et al (2017) and Bhuvaneshwari et al (2015) found that when botanical pesticides (BPs) are used, they have the following effects: they can kill the pest, disrupt its physiology and development, keep it away from the surface, or cause the plant to acquire induced systemic resistance. In previous studies, main challenges in common bean production include pests, highly pesticide costs (Kasina, 2003 andMonda et al, 2003), therefore, the present study offer the important role of botanical-based pesticide and natural predator in IPM program in common bean crop.…”
Section: Common Bean Yieldmentioning
confidence: 99%